(untitled) (Marketing Journal, 2025)
This article analyzes the foreign experience of applying artificial intelligence (AI) technologies in small businesses and explores opportunities for their implementation in Uzbekistan . The study examines best practices from the USA, Germany , South Korea , India , Israel , and other countries , highlighting possible ways of adapting them to local conditions . The paper systematically identifies key challenges in introducing AI into Uzbekistanʼs small business sector , including infrastructure limitations , shortage of skilled professionals , financial constraints , and market differences . Finally , a roadmap and policy recommendations are proposed for the effective integration of AI in small business development . 91